Systematic review of human listeriosis in China, 1964–2010. Issue 10 (10th September 2013) - Feng, Yanfang; Wu, Shuyu; Varma, Jay K.; Klena, John D.; Angulo, Frederick J.; Ran, Lu
Abstract: Objectives: Listeria is an important foodborne pathogen with severe manifestations and high case‐fatality rate. However, listeriosis is not yet a notifiable disease in China, and there is no national monitoring system for cases. We conducted a systematic review to better understand the clinical and epidemiologic features of listeriosis in China. Methods: Both electronic and manual retrieval systems were used to search Chinese literature for cases and isolates of human listeriosis reported between 1964 and 2010. We recorded and analysed demographic, clinical and laboratory information available for reported cases. Results: A total of 147 clinical cases, 479 Listeria isolates and 82 outbreak‐related cases were reported in 28 (90%) provinces in China from January 1964 to December 2010. Of the clinical cases, 45 (31%) were central nervous system infections, 68 (46%) were septicaemia and 34 (23%) were focal infections or gastroenteritis. The overall case‐fatality rate was 26% (34/130) among clinical cases with known outcomes and 46% (21/46) among neonatal cases. Conclusion: Listeriosis cases occurred in China throughout the study period between 1964 and 2010. Case‐fatality was similar to published data from other countries. China should consider requiring notification of listeriosis cases to improve estimates of incidence, identification of risk factors and design of preventive measures.